Windows on early Christianity : uncommon stories, striking images, critical perspectives - Aageson, James W., 1947- (Wipf and Stock Publishers, 2016)
This book is introductory, but it is not an introduction to biblical content or to the history of early Christianity in the typical sense. Each of the chapters addresses a different aspect of the material and provides its own perspective on the origin of the church and early Christianity. The chapters begin with questions that in turn focus the discussions. The chapters can be read as independent, freestanding arguments and can be mixed and matched, enabling readers to investigate the respective topics independently. However, the chapters also follow a logical narrative line. In addition, imag.